Effectiveness of a daily reminder through short message service (SMS) for medication adherence to oral antibiotics among adult Filipino outpatients of a tertiary government hospital in Metro Manila: a randomized controlled study - Medenilla, Daniel R.; Rodriguez, Ricco N.; Ruizal, Erica Faith P.; Gutierrez, Margarita M. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2024)
Introduction: Non-adherence to oral antibiotics often leads to therapeutic failure, aggravation of infection, and antimicrobial resistance. One of the most common reasons for non-adherence is forgetting to take medications as prescribed. Short message service (SMS) reminders have been proven to be an effective intervention to address non-adherence; however, its effect on short-term oral antibiotic adherence has not yet been studied.

Objective: This study aims to evaluate the effectiveness of a daily SMS medication-taking reminder on medication adherence to oral antibiotics among adult Filipino outpatients who obtained their oral antibiotics from a tertiary government hospital.

Methods: A two-arm, parallel, non-blinded randomized controlled trial was conducted with the primary outcome of medication adherence to short-term antibiotics, expressed in pill count. Interviewer-administered questionnaires were utilized to survey participants on potential confounders at the start and end of their antibiotic therapy. Participants were randomly allocated to study groups following a 1:1 ratio, wherein the intervention group received standardized SMS reminders throughout the duration of their therapy while the control group received no reminders. After therapy, adherence to oral antibiotics were measured along with the potential confounders.

Results: The results showed that the SMS reminder intervention improved medication adherence but was not statistically significant. Confounders that significantly influenced the likelihood of adherence include filling of prescription (P = 0.030), number of symptoms (P = 0.044), and duration of therapy (P = 0.010). However, the models generated have low goodness of fit attributed to the resulting sample size only reaching 35.65% of the target.

Conclusion: SMS medication-taking reminders may be beneficial in improving adherence of adult Filipino outpatients. Partially filling prescriptions and longer duration of therapy were predictors of non-adherence, while a higher number of symptoms improved likelihood of adherence. Given the current sample size, findings are inconclusive and further research is required.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2024
Keywords: Randomized Controlled Trials -- Outpatient medical care -- Antibiotics; Medication adherence -- Short message service -- (Manila) Philippines; Health services accessibility -- Hospital services -- Philippines .; Short-term antibiotics .; Medication adherence; SMS reminders, .; Outpatients